RISK MANAGEMENT AND BANK PROFITABILITY: EVIDENCE FROM NIGERIAN DEPOSIT MONEY BANKS - Lukman Adebayo Oke ABDULRAUF (Malete Journal of Accounting and Finance, 2023)
Risk management issues in the banking sector do not only have greater impact on bank profitability but also on national economic growth and the general business development. The bank’s motivation for risk management comes from those risks which can lead to underperformance. This study seeks to assess the impact of risk management on banks profitability in Nigeria. To achieve this, the study covered 6 years ranging from 2012-2017. Also, twelve deposit money banks were chosen as sample from the whole Nigeria DMBs. Audited annual financial statements of the selected banks for the years were used in obtaining data for the purpose of this research. The independent variable which is Risk Management is proxied as Non-Performing Loan Ratio (NPLR), Capital Adequacy Ratio (CAR) and Loan-to-Deposit (LTD) while the dependent variable which is profitability was measured as return on assets (ROA). Using panel random effects regression, the results revealed that non-performing loan ratio has a negative effect and it is statistically significant at 5% on banks profitability, and Loan-to-Deposit ratio is also statistically significant at 5% and have positive effects on banks’ profitability while capital adequacy ratio is insignificant. The study concluded that risk management in terms of non-performing loan ratio and loan-to-deposit ratio has significant effect on banks’ profitability. The study therefore recommended that the banks’ management should do more in the area of controlling the rate at which subprime loans are given out, in order to mitigate the risk of future loss on non-performing loan. Also, banks should further implement more policies that support increased lending to customers, especially the more credit worthy ones, in order to increase returns and performance.